2017
DOI: 10.1016/j.ydbio.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Genomic determinants of epidermal appendage patterning and structure in domestic birds

Abstract: Variation in regional identity, patterning, and structure of epidermal appendages contributes to skin diversity among many vertebrate groups, and is perhaps most striking in birds. In pioneering work on epidermal appendage patterning, John Saunders and his contemporaries took advantage of epidermal appendage diversity within and among domestic chicken breeds to establish the importance of mesoderm-ectoderm signaling in determining skin patterning. Diversity in chickens and other domestic birds, including pigeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 94 publications
0
21
0
Order By: Relevance
“…We previously demonstrated that in pigeons, the grouse phenotype is associated with a cisregulatory mutation that reduces PITX1 expression in the HH25 HL, while the muff phenotype is associated with cis-regulatory mutations that cause a combination of PITX1 reduction and ectopic TBX5 expression in the HH25 HL (Domyan et al, 2016, Boer et al, 2017. To determine if PITX1 and TBX5 expression differs in scaled, grouse, and muff HLs at other stages of development, we measured PITX1 and TBX5 expression in HH21, HH25, and HH29 HL buds by quantitative reverse-transcriptase PCR (qRT-PCR) (Supplemental Figure 2).…”
Section: Dynamic Tbx5 and Pitx1 Expression Differences Characterize Fmentioning
confidence: 99%
“…We previously demonstrated that in pigeons, the grouse phenotype is associated with a cisregulatory mutation that reduces PITX1 expression in the HH25 HL, while the muff phenotype is associated with cis-regulatory mutations that cause a combination of PITX1 reduction and ectopic TBX5 expression in the HH25 HL (Domyan et al, 2016, Boer et al, 2017. To determine if PITX1 and TBX5 expression differs in scaled, grouse, and muff HLs at other stages of development, we measured PITX1 and TBX5 expression in HH21, HH25, and HH29 HL buds by quantitative reverse-transcriptase PCR (qRT-PCR) (Supplemental Figure 2).…”
Section: Dynamic Tbx5 and Pitx1 Expression Differences Characterize Fmentioning
confidence: 99%
“…39 In addition, it is common in birds to find variable feathering patterns throughout the body: micropatterns and macropatterns. 40 Micropatterns are variations in the kind of integumental features (as in types of feathers); there are different types in different zones of the body. Macropatterns relate to integumental organization in certain parts of the body, like the absence or presence of feathers in certain areas, as is the case in the "naked neck" chicken breeds 41 and ptarmigans (Lagopus), in which foot feathers are common even in juveniles ( Figure 3C).…”
Section: Integumental Traits: Variation and Developmentmentioning
confidence: 99%
“…68 For example, the seminal work of Saunders, 69,70 which involved grafting and assessing the interactions between different body regions of chickens throughout development, provided a foundation for further developmental studies on this matter. 40 Traits such as combs, wattles, egg teeth, and feathers are appendages that form via outgrowth of the ectodermal epidermis (ie, epithelium), and are induced and patterned by the prospective dermis (ie, mesenchyme). 71 However, the dermis comes from different origins: neural crest in the head or mesoderm in the limbs and trunk.…”
Section: Integumental Traits: Variation and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…By sequencing many pigeon genomes, Shapiro identified mutations associated with particular pigeon traits and is pursuing developmental studies to elucidate the function of those genes. These studies are revealing how pleiotropic effects such as increased fat deposition and vision problems appear in some types of pigeons (Boer, Van Hollebeke, & Shapiro, ). Cheng Ming Chuong (University of Southern California) talked about the evodevo of feather coloration.…”
Section: Color Pattern Evolutionmentioning
confidence: 99%